Standardization of red onion methanolic extract to detection of phosphorylated proteins in sds-page - Rodríguez-Cavallo, Erika; Arrieta Vergel, Karen; Gaviria Figueroa, Isis; Marrugo-Padilla , Albeiro; Méndez-Cuadro, Darío (Revista Productos Naturales, 2022)
Protein phosphorylation is a reversible post-translational modification, associated with countless vital cell processes such as signal transduction, cell differentiation, development, cell cycle control and metabolic pathway regulation.
Keywords: Antioxidants; flavonoids; fruits; protein carbonylation